Kajian Konseptual Arsitektur Masjid Babah Alun Desari sebagai Manifestasi Akulturasi Budaya - Buchori, Muhammad Ilham; Azwar, Juliana; Sulaiman, Madrin; Rahardjo, Astrid Hapsari; Ibadi, Raden Mohamad Wisnu (CV. Gio Architect, 2025)
In architecture, a concept serves as the fundamental idea that guides the entire design process—integrating function, form, symbolism, and cultural context. This study examines how such a concept is manifested as a form of architectural acculturation in the Babah Alun Desari Mosque, Cilandak, a contemporary Indonesian mosque that harmoniously blends Islamic spatial values with Chinese aesthetic traditions. The research aims to identify and analyze how the architectural concept of acculturation is implemented through the mosque’s visual composition, ornamentation, and spatial arrangement. A qualitative descriptive approach was employed through literature review and case study methods, involving visual observation, documentation, and theoretical analysis related to architectural concepts and cultural synthesis. The findings of this study reveal that the curved roof crowned with a dome, the presence of dragon and floral ornaments, and the open, inclusive spatial configuration represent tangible manifestations of architectural acculturation. From a distance, Chinese architectural identity appears more dominant, while Islamic character becomes more evident upon approaching the prayer hall. Thus, the Babah Alun Desari Mosque stands as a manifestation of architectural acculturation, harmonizing Eastern aesthetics with Islamic spirituality within Indonesia’s multicultural urban context.